HUBUNGAN BENTUK PRILAKU BULLYING DENGAN TINGKAT STRES PADA REMAJA KORBAN BULLYING - Andriani, Novia; Elita, Veny; Rahmalia, Siti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Teenage is the culmination of bullying behavior and can affect both boys and girls. The most visible effectsof bullying are stress and depression. This study aimed to determine the relationship between the form ofbullying behavior and the stress levels in teenagers bullying victims in one SMPN Pekanbaru in descriptivecorrelational research design and by applying cross-sectional approach. The sample was 82 respondentstaken using total sampling technique. Questionnaires were the instruments used for variable forms ofbullying behavior and stress levels. The data was analyzed by applying Kolmogorov-Smirnov test. Theresearch on the relationship of bullying behavior form and stress level on teenager bullying victim showedthat p-value = 0,060> α = (0,05), so it can be concluded that there was no significant relationship betweenthe form of bullying behavior and stress level in teenager victims of bullying in one of SMPN Pekanbaru.This research can be used as a foundation of information and additional insight about the form of bullyingbehavior and stress level in teenager bullying victim as well as a reference in prevention of bullyingbehavior that has been happening in society, especially teenagers in one SMPN Pekanbaru.Keywords : Bullying, school, stress, teenager, victims